Pregnancy outcomes among daycare employees in Finland - Riipinen, Anita; Sallmén, Markku; Taskinen, Helena; Koskinen, Aki; Lindbohm, Marja-Liisa (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVE ': 'The aim of this study was to investigate whether working as a daycare employee increases the risk of perinatal death, pre-term birth, low birth weight, smallness for gestational age, or congenital malformations. ' ' METHODS ': 'We conducted a register-based cohort study among daycare employees and women from various occupations of healthcare (reference group). Study subjects were identified from the files of Finnish trade unions and the National Authority for Medicolegal Affairs. Pregnancy outcomes, antenatal occupation, and working status were obtained by linkage to national registers. The final data consisted of 13 299 and 12 182 singleton births in the study and reference groups, respectively. We analyzed pregnancy outcome data using generalized estimating equations and linear regression. ' ' RESULTS ': 'The occurrences of pre-term birth [odds ratio (OR) 0.91, 95% confidence interval (95% CI) 0.79–1.06], perinatal death (OR 0.91, 95% CI 0.62–1.34), smallness for gestational age (OR 1.01, 95% CI 0.91–1.12), and congenital malformation (OR 1.10, 95% CI 0.92–1.32) were similar among the children of the daycare employees and the reference group. The adjusted mean birth weight of the children of the daycare employees was slightly higher (14 g, 95% CI -1–29) than that of the reference group, but the difference was attenuated to 6 g in the subset of the first births. ' ' CONCLUSION ': 'Daycare employees were not, in general, at an increased risk of an adverse pregnancy outcome. However, efforts should nevertheless be made to prevent their exposure to harmful viruses and heavy physical load during pregnancy.
Keywords: birth; birth weight; congenital malformation; daycare; daycare employee; death; employee; Finland; gestational age; malformation; perinatal death; pre-term birth; pregnancy; pregnancy outcome; SGA; smallness for gestational age; weight